Esterioides sexuales del embarazo y sensibilidad tisular a los irritantes locales en el periodonto - Quinchía-R., Beatriz Helena; Agudelo-J., Bernardo; Berdugo, Jesús Alfredo; Ossal-L., Jorge Eliécer (Revista Facultad de Odontología Universidad de Antioquia, 2017)
The aim of this review is to argue that the oral manifestations asociated to hormonal variations during the reproductive cycle, in humans, indicdte that the periodontum is a target tissue for hormonal influence. The sex steroid hormones: Estradiol, Progesterone and Androgens have important functions on the expression of secondary sexual characteristics, defined the sexual development of the individual and the reproductive processes. The increase in circulating hormones could affect the metabolic functioning of other organs and tissues. Fibroblasts are the math cell in cytoarchitecture of the peridontum, but the direct response of these cells to hormonal stimuli has not been studied deeply. The objective of this essay is to review the literature on this subject and we conclude that the hormonal status of pregnancysensitizes the periodontal tissues to bacterial insult. It is unknown how the hormonal environment of pregnancy may affect the response of periodontal fibroblasts; this would partially explain the incidence of periodontitis during gestation.